Karyological studies in Hariana, Holstein Friesian and their crossbreds* - NAGPURE, N S; PAWDE, A M; KOUL, G L (The Indian Journal of Animal Sciences, 2014)
Cytogenetic studies were undertaken in 3 breed groups of cattle, viz, Hariana, Holstein Friesian and their crossbreds, to characterize these breed groups, Blood samples were collected from animals maintained at LPM (C&B) farm, IVRI, Izatnagar. Short term whole blood lymphocyte culture was carried out and metaphase spreads were obtained using standard techniques, The diploid number of chromosomes in the animals was 2n=60 (58 autosomes and 2 sex chromosomes). X chromosome was submetacentric and Y chromosome was acrocentric in Hariana and submetacentric in Friesian and crossbreds. The relative length (RL) of auto somes varied from 6,04+-0.14 to 1.66+-0.07 in Hariana; 5.98+-0.04 to 1.63+-0.08 in Friesian and 5.92+-0.09 to 1.90+-0.13 in crossbreds. The comparison of morphology and relative length failed to bnng out the major karyological differences among the breed groups studied.